Analisis Usahatani Padi Sawah di Kelurahan Imandi Kecamatan Dumoga Timur - Salea, Marvyanty Wanda; Katiandagho, Theodora Maulina; Rori, Yolanda Pinky Ivana (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2025)
This study aims to analyze the feasibility of wet-rice farming in Imandi Village through the parameters of total cost, revenue, income, and R/C Ratio. The research was conducted from April to June 2024 using primary data obtained through structured interviews with 12 farmer respondents who are members of the Manunggal farmer group (purposive sampling) and secondary data from the literature and related agencies. The results of the analysis showed that the cost of paddy rice farming reached Rp11,005,008 per hectare and Rp17,424,596 per respondent during one growing season. The revenue earned amounted to Rp26,993,546 per hectare and Rp42,739,782 per respondent, resulting in a net income of Rp15,988,538 per hectare and Rp25,315,186 per respondent. The R/C ratio value of 2.45 indicates that rice paddy farming in the research location is feasible and profitable. Break-Even Point (BEP) analysis showed a unit BEP of 65.06 kg per hectare and 103.012 kg per respondent, while the rupiah BEP was recorded at Rp845,980 per hectare and Rp1,339,249 per respondent. The findings recommend that the development of paddy rice farming in Imandi Village has good economic prospects, supported by cost efficiency and optimal productivity.